Ensuring patient safety: Best practices in medical device software development based on IEC 62304 - Casma Angulo, Pablo Ivan (2025)
Medical device software plays a crucial role in modern healthcare, responsible for a wide range of functions, from monitoring vital signs to administering treatments. However, software failures can have serious consequences, including patient death. In response to this situation, the IEC 62304 standard establishes a set of processes and requirements designed to ensure the safety and effectiveness of software used in medical devices, mitigating the risks associated with their use. In this article we explore the importance of developing medical software under the guidelines of IEC 62304, focusing on patient protection, risk identification and management and the implementation of good practices throughout the software life cycle, the objective of the article is to provide good practices for the development of software for medical equipment, based on the IEC 62304 standard, in order to ensure safety and reliability, we complement with the presentation of an implementation plan that focuses on the objectives of the process, the activities to be carried out and the required documentation, which is key to a certification and registration process with the FDA, As a result we present an assessment from the risk in the adoption of the standard, as well as statistics of the main failures presented in devices that have not followed the recommendations of the standard and as a conclusion we present the advantages and disadvantages in compliance with the standard.